Survivors and the suicide attempt recurrence (Acta Scientiarum. Health Sciences, 2023)
We aimed at analyzing suicide attempt recurrence from the perspective of survivors. We performed a qualitative and descriptive study between 2017 and 2019 at an Emergency Care Unit. The sample was defined by acceptance to participate, with 80 people who were in care for recurrence of suicide attempt. We used a semi-structured interview method and processed data through thematic content analysis. Participants' reported histories ranged from one to eight suicide attempts; with finding a way out to relieve the experienced pain and suffering being the main alleged reason. The yearning for dying and ceasing suffering, as well as the drive for living, were both present in the characteristic ambivalence of the participants. Suicide attempt recurrence is related to the inflexible and neglecting mindset towards psychosociocultural conditions of our health system, which offers unsatisfactory treatment to post-suicide attempt citizens, revealing the inability to solve adversities.